Factors Affecting the Success of Treatment in Drug Sensitive Pulmonary Tuberculosis Patients at the Rimba Jaya Health Center Merauke Regency - Frengky Apay; Rohmani Rohmani (Science Midwifery, 2022)
Tuberculosis (TB) is an infectious disease as a major cause of health problems. TB is one of the top 10 causes of death worldwide caused by the bacterium Mycobacterium tuberculosis. A quarter of the world's population has been infected with Mycobacterium tuberculosis. Diagnosis and timely treatment of routinely taking anti-tuberculosis drugs (OAT) for the first six months in TB patients can be cured and the transmission of infection is decreasing. . Research Methods: This research is an analytic observational with a cross sectional design. The results of this study were that most of the respondents aged between 20-35 years amounted to 29 people (58%). The gender of the majority of women amounted to 28 people (56%). Most of the education is SMA with 28 people (56%). Most of the occupations are college students, students and not working totaling 19 people (38%). The knowledge of the respondents is good amounting to 32 people (64%). Most of the economic status is moderate amounting to 28 people (56%). Most of the access to treatment is close, amounting to 48 people (96%). Most of the PMO types are families with 46 people (92%). Most of the PMO roles were good, amounting to 44 people (88%). Most of the drug sensitive people were drug sensitive 6 months totaling 45 people (90%). There are 3 factors that influence the success of Pulmonary TB Treatment at the Rimba Jaya Health Center, namely education, economic status and access to treatment. Meanwhile, those that do not affect the success of drug-sensitive pulmonary TB treatment are age, gender, occupation, type of PMO, role of PMO, knowledge. The conclusion of this study is that there are 3 factors that influence the success of Pulmonary TB Treatment at the Rimba Jaya Health Center, namely education, economic status and access to treatment. Meanwhile, those that do not affect the success of drug-sensitive pulmonary TB treatment are age, gender, occupation, type of PMO, role of PMO, knowledge.